Microwave-Assisted Hydrothermal Synthesis of Zinc-tin Based Nanoflower for the Adsorptive Removal of Cadmium from Synthetic Wastewater - Toprak, Muenevver; Yildiz, Baris; Zaman, Buse Tugba; Bozyigit, Gamze Dalgic; Temuge, Ilknur Durukan; Cetin, Guelten; Bakirdere, Sezgin (SPRINGER INT PUBL AG, 2024)
The present study utilized zinc-tin nanoflowers (ZT-NFs) in a batch adsorption treatment process to effectively remove cadmium from synthetic wastewater. The batch adsorption strategy was optimized using the univariate approach to enhance the efficiency of the adsorption process. The dominant parameters examined in the optimization experiments were pH/volume of buffer solution, nanoflower amount, and sample agitation type/period. After determining the optimal batch adsorption conditions, equilibrium studies were performed by adding cadmium to synthetic wastewater at concentrations in the range of 1.0 - 40 mg/L. The quantification accuracy for cadmium was improved by developing the calibration plot with spiked sample matrix. The equilibrium data were subjected to mathematical modelling utilizing the Langmuir adsorption isotherm model. The calculated isotherm constants indicated a well-fitted isotherm model to the experimental data. The reported ZT-NFs-based adsorptive removal strategy was effectively employed to remove cadmium from synthetic wastewater.
Keywords: Adsorption; Cadmium; Langmuir isotherm; Synthetic wastewater; Zinc-tin oxide nanoflower; ATOMIC-ABSORPTION-SPECTROMETRY; SOLID-PHASE EXTRACTION; DESIGN; PRECONCENTRATION; EFFICIENT; SAMPLES; IONS; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources